2017
DOI: 10.3126/bibechana.v15i0.18344
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of structural, electronic and magnetic properties of Co-based quaternary Heusler compounds: CoFeCrAl, CoFeTiAs, CoFeCrGa and CoMnVAs

Abstract: We study the structural, electronic and magnetic properties of Co-based LiMgPdSn-types of quaternary Heusler compounds (CoFeCrAl, CoFeTiAs, CoFeCrGa, and CoMnVAS) using Density Functional Theory (DFT) implemented on Tight Binding Linear Muffin-Tin Orbital within Atomic Sphere Approximation (TB-LMTO-ASA) Code. The optimized value of lattice parameter for CoFeCrAl, CoFeTiAs, CoFeCrGa and CoMnVAs are found to be 5.61A˚, 5.76 A˚, 5.61A˚ and 5.71A˚ , respectively. From the calculation of electronic band structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several theoretical models (Anusionwu et al, 1998;Prasad et al, 1998;Akinlade et al, 2002;Novakovic, 2010;Kumar et al, 2013;Koirala et al, 2013;Singh et al, 2014) have long been proposed to understand the thermodynamic, structural, transport and surface properties of binary liquid alloys. The computational models for the calculation of band structure calculations for binary, ternary and quaternary alloys have also proposed by various authors (Pandey et al, 2014;Poudel & Kaphle, 2016;Kaphle et al, 2012Kaphle et al, & 2015Pandey & Kaphle, 2017;Ghimire et al, 2016;Sharma and Kaphle, 2017;Sedhain and Kaphle, 2017). In present work, we study the concentration dependent mixing properties of liquid Ag-Au at 1350K by the simple statistical model (Singh et al, 1990;.…”
Section: Introductionmentioning
confidence: 85%
“…Several theoretical models (Anusionwu et al, 1998;Prasad et al, 1998;Akinlade et al, 2002;Novakovic, 2010;Kumar et al, 2013;Koirala et al, 2013;Singh et al, 2014) have long been proposed to understand the thermodynamic, structural, transport and surface properties of binary liquid alloys. The computational models for the calculation of band structure calculations for binary, ternary and quaternary alloys have also proposed by various authors (Pandey et al, 2014;Poudel & Kaphle, 2016;Kaphle et al, 2012Kaphle et al, & 2015Pandey & Kaphle, 2017;Ghimire et al, 2016;Sharma and Kaphle, 2017;Sedhain and Kaphle, 2017). In present work, we study the concentration dependent mixing properties of liquid Ag-Au at 1350K by the simple statistical model (Singh et al, 1990;.…”
Section: Introductionmentioning
confidence: 85%
“…Apart from Co-based HAs, it has been recently predicted that some Heusler families, including the full-HAs based on vanadium, are half-metallic ferromagnets and are suitable for thermo-spintronics application [5,32,33]. Pandey et al reported QHA CoMnVAs [34] and other authors also have reported similar kinds of compounds like CoCrScSn by Zang et al [35,36]. Motivated by these findings, we focused in this report on predicting Co based QHAs made from 3-d transition metals ScVCoZ (Z = Si, Ge, Sn, P, As, and Sb) (SVCZ).…”
Section: Introductionmentioning
confidence: 99%